2016
DOI: 10.1002/ptr.5604
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Plant Food Supplements and Plants Consumed as Food: Results from the Poisons Centres-Based PlantLIBRA Study

Abstract: Plant food supplements (PFS) are products of increasing popularity and wide-spread distribution. Nevertheless, information about their risks is limited. To fill this gap, a poisons centres-based study was performed as part of the EU project PlantLIBRA. Multicentre retrospective review of data from selected European and Brazilian poisons centres, involving human cases of adverse effects due to plants consumed as food or as ingredients of food supplements recorded between 2006 and 2010. Ten poisons centres provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 37 publications
(75 reference statements)
1
40
0
1
Order By: Relevance
“…Caffeine is known to exhibit cardiovascular activity, while p-synephrine is not. Lude et al (2016) reviewed plant food supplements associated with a large number of plants including C. aurantium involving human adverse case reports. These authors referenced most of the case studies reviewed in the preceding texts (Stohs, 2010) and cited review articles that made reference to the same case studies.…”
Section: Summary Of Previous Reviewsmentioning
confidence: 99%
“…Caffeine is known to exhibit cardiovascular activity, while p-synephrine is not. Lude et al (2016) reviewed plant food supplements associated with a large number of plants including C. aurantium involving human adverse case reports. These authors referenced most of the case studies reviewed in the preceding texts (Stohs, 2010) and cited review articles that made reference to the same case studies.…”
Section: Summary Of Previous Reviewsmentioning
confidence: 99%
“…Based on a multi‐center retrospective review of data from European and Brazilian poison centers gathered between 2006 and 2010, G. glabra had been reported as 1 of the 10 most frequently plant foods that caused adverse effects (Lüde et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The safety of botanical medicines has been documented in various traditional systems of medicine such as Ayurvedic Medicine and Traditional Chinese Medicine over centuries. Recent retrospective and systematic reviews in the European Union and South America have concluded severe adverse events associated with Botanical Medicine usage were rare (39,40).…”
Section: Introductionmentioning
confidence: 99%